The Role of Perceived Ease of Use, Trust, Product Knowledge and Perceived of Convenience on Intention to Use of Sharia Banking Card - Muhammad Risal Tawil; Muhammad Subandi; Moch Arif Hernawan; Prety Diawati; Kraugusteeliana K (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this research is to analyze the effect of perceived usefulness, perceived convenience, product knowledge and trust partially on the intention to use the sharia banking card, to analyze the effect of perceived usefulness, perceived convenience, product knowledge and trust simultaneously on the intention to use the sharia banking card and to find out which variable most influences interest in using a sharia banking card. The scope of this research is the people of DKI Jakarta who are interested in using sharia credit cards. The variables used in this study are perceived usefulness (X1), perceived ease of use (X2), product knowledge (X3) and trust (X4) as independent variables, and interest in using (Y) as the dependent variable. This research was conducted on residents of DKI Jakarta who are interested in using Islamic credit cards. The sample is part of the number and characteristics possessed by the population. influence of each independent variable Perceived Usefulness, Perceived Convenience, Product Knowledge and Trust on interest in using the sharia banking card is the variable Perceived Usefulness does not affect interest in using the sharia card. Perceived ease of variable influences interest in using the sharia card. The Product Knowledge Variable influences the interest in using the sharia card.